Study Effect of Kinetin, Bio-fertilizers and Organic Matter Application in Lettuce under Salt Stress - Zaahra. Z. Majid (Journal of Global Pharma Technology, 2018)
Salinity causes cellular damage and limits crop productivity, by reduces water availability of plant roots via negative osmosis potential, salinity affects. The present study aims to mitigate the adverse effects of soil salinity in lettuce through organic composts like Plam fronds and Rice wastes   with exogenous applications like Kinetin and Bio-fertilizers. field experiment designed  to study the effect of irrigation water quality ,organic composts  ,kinetin and Bio-health application in N.P and K contents in leaves and anti-oxidant enzymes activity  of lettuce  , The experiment included 54 treatments with three factors  The first factor represents the salinity of irrigation water (W) at two  levels (1.2,  6.1) ds m-1 ), The second factor represents the kinds of organic composts (Palm fronds and Rice wastes) 20 ton /hectare to each one. The third factor represented the kinetin application (50 mg.L-1) and Bio-Health fertilizers (5kg/ hectare). The results show elevated water salinity levels led to elevation in activity of POX ,CAT, MDA,SOD enzymes and proline contents in leaves, while resulting decrease in leave contents of ( N.P.K) and the total yield, marketing yield and marketing head weight, Organic composts , kinetin and bio-health applications alleviated from the negative effects of saline water by increasing the total yield, marketing yield and marketing head weight and  (NPK) contents in leaves ,reduced POX ,CAT, MDA,SOD and proline ,except bio-health applications increased POX ,CAT, MDA,SOD  activities, That possible to mitigation the negative effect of salt stress by some application like exogenous plant growth Regulators , bio fertilizers and decomposed organic matter to solve the disruption of endohormons and lack of available nutrients under salt stress, and elevation of osmotic stress in soil solution in roots area, the study applications improved the growth and it has increased the lettuce tolerance to the salt  stress.Keywords: Salt stress, lettuce, Kinetin, Organic composts, Bio-heath, bio-fertilizers.